The middle-income trap – definitions, theories and countries concerned: A literature survey - Linda Glawe; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2016)
In recent years, a growing body of economic literature has focused on the phenomenon of the so-called middle-income trap (MIT). The term usually refers to countries that have experienced rapid growth and thus quickly reached middle-income status, but then failed to overcome that income range to further catch up to the developed countries. This paper surveys the MIT literature. It begins by laying out different approaches to defining the MIT (with a focus on the distinction between absolute and relative approaches) and by presenting as well as classifying the most important empirical studies. After a short overview of the currently identified MIT countries, the article summarizes the main explanatory approaches, taking into account both the theoretical foundations and the empirically identified triggering factors.
urn:nbn:de:hbz:708-dh4716
Keywords: O10; O40; 330; middle-income trap; middle-income countries; economic growth; economic development; growth slowdowns; catching up